The future of 3D food printing in the Philippine Food Industry by 2030 a technology foresight - Ronquillo, Angelique F.; Imbang, Glen A. (Quezon City University of the Philippines Diliman, Technology Management Center, 2016)
This special project presents a technology foresight on the future of the Philippine food industry using scenario building exercise to assess the adoption of 3D food printing technology in the next 15 years (2016-2030).
An overview of trends in the external environment and food industry sector were determined through analysis of sociocultural, technological, economic, environmental, and political (STEEP) factors. The current scenario of the food industry was assessed through analysis of strengths, weaknesses, opportunities, and threats (SWOT). Information obtained from STEEP and SWOT analyses were used to determine the key driving forces of the food industry. Among the major driving forces identified were: government support, cultural acceptance, consumer behavior, and policies and regulations.
Based on the identified driving forces, scenarios were developed to help key decision-makers on strategizing for future technology adoption. The four scenarios are : (1) Prometheus Unbound, (2) Dominance of Dysnomia, (3) The Achilles Heel, (4) The Labyrinth of Daedalus, and (5) The Revival of Ambrosia. The "Prometheus Unbound" scenarios are based on strong government support and wide cultural acceptance on the technology. On the other hand, the "Dominance of Dysnomia" scenario pertains to the missed opportunity of the government to take advantage of the technology's possible transformation of the food industry due to the unrecognition of the technology's potential. "The Achilles Heel" scenario depicts the influence of cultural rigidity on the overall technology adoption. "The Labyrinth of Daedalus" scenario presents a case of technological backwardness resulting from unfocused government priorities coupled with cultural rigidity. Lastly, the "The Revival of Ambrosia" scenario presents the exploration of 3D food printing in medical foods application, as supported by cultural acceptance and intensified government efforts to drive and protect its manufacturing and distribution.
Among the developed scenarios, the "Prometheus Unbound" and "The Revival of Ambrosia" scenario depicts the most plausible and favorable futures for the Philippine food industry. These can be used as a basis for formulating strategic decisions and action plans which can significantly affect the future of the Philippine food industry with the application of 3D food printing technology.
Thus, for the Philippine food industry to achieve the most plausible and favorable scenarios, actions must be taken upon to address the foreseen drivers which may present the greatest uncertainties : (1) the Philippine government must take upon its critical role in revamping the framework of the local food industry, and (2) challenges in cultural acceptance must be overcome. Specific strategies to support these were also recommended.
In partial fulfillment of the requirements of TM 299
Thesis
Keywords: Three-dimensional modeling; Food industry -- Philippines